Effectiveness of cyclin-dependent kinase 4 and 6 inhibitors for the treatment of hormonesensitive HER2-negative metastatic breast cancer in first-line therapy: A systematic literature review - N. A. Avxentyev; I. I. Andreyashkina; E. V. Artamonova; L. V. Bolotina; E. I. Kovalenko; N. N. Sisigina (Опухоли женской репродуктивной системы)
At present, cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors such as palbociclib, ribociclib, and abemaciclib are widely used for the first-line treatment of locally advanced or metastatic breast cancer. However, direct comparisons of these treatment options in randomized studies have not been conducted.Aim of the work is to gather and analyze published data on the comparative effectiveness of CDK4/6 inhibitors in combination with aromatase inhibitors in postmenopausal patients with HR+/HER2– locally advanced or metastatic breast cancer. A systematic review of publications presenting results from original studies on the impact of CDK4/6 inhibitor therapy in combination with aromatase inhibitors on the survival of patients was performed. Nineteen studies with original data on progression-free survival and overall survival were identified. None of the studies found significant differences between different CDK4/6 inhibitors and aromatase inhibitors in terms of progression-free survival. A statistically significant superiority of ribociclib over palbociclib in terms of overall survival was observed in a single matching-adjusted indirect comparison, while seven other studies of various types (real-world data studies, matching-adjusted indirect comparisons, and meta-analyses) did not find significant differences between the investigated drugs in terms of overall survival.Currently, there is no compelling evidence of the superiority of one CDK4/6 inhibitor over others. The decision on the preference for a specific drug within the class can only be made after conducting direct randomized comparison trials, or accumulating sufficient real-world data on the use of palbociclib, ribociclib, and abemaciclib.